Implementing Integrated Performance Assessment (IPA) as a Learning Strategy to Enhance the Students’ Writing Skill for Seventh Graders - Nurul Koidah (Language Circle: Journal of Language and Literature, 2025)
This study explores the implementation of the Integrated Performance Assessment (IPA) model as a learning strategy to improve the writing skills of seventh-grade students at SMP Muhammadiyah 04 Sukorejo. The IPA emphasizes integrating interpretive, interpersonal, and presentational communication modes. Using a mixed-methods design, both quantitative and qualitative data were gathered through pretests, posttests, questionnaires, and interviews. The study followed the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—to create and assess IPA-based instructional materials. Results from SPSS analysis showed a significant improvement in students’ writing performance, with posttest scores (M = 79.80) significantly higher than pretest scores (M = 55.53), p < .001. Qualitative data indicated that students found the IPA-based worksheets engaging and helpful, while the teacher noted that IPA supported integrated skill learning and authentic assessment. Theoretically, the findings confirm IPA’s potential to promote linguistic, cognitive, and affective development by linking assessment with instruction. Pedagogically, this research demonstrates that IPA is an effective and practical framework for enhancing EFL learners’ writing skills through authentic, task- based, and scaffolded activities. The study recommends further development of IPA-based materials into comprehensive teaching resources to support writing instruction in secondary EFL contexts.